2007
DOI: 10.1128/aac.01318-06
|View full text |Cite
|
Sign up to set email alerts
|

Population Pharmacokinetics and Pharmacodynamics of Continuous versus Short-Term Infusion of Imipenem-Cilastatin in Critically Ill Patients in a Randomized, Controlled Trial

Abstract: Beta-lactams are regularly administered in intermittent short-term infusions. The percentage of the dosing interval during which free drug concentrations exceed the MIC (fT >MIC ) is the measure of drug exposure that best correlates with clinical outcome for beta-lactams. Therefore, administration by continuous infusion has gained increasing interest recently. We studied 20 critically ill patients with nosocomial pneumonia and investigated whether continuous infusion with a reduced total dose, compared to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
140
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(148 citation statements)
references
References 32 publications
8
140
0
Order By: Relevance
“…A tobramycin concentration of 4 mg/liter and isepamicin concentrations of 8 to 16 mg/liter represent the average unbound plasma concentrations in humans over a 24-h dosing interval for tobramycin at 7 mg/kg of body weight and 15 or 25 mg/kg isepamicin given once daily (17,26). Additional experimental arms with 12 mg/ liter tobramycin and 64 mg/liter isepamicin represent the average free plasma concentration of aminoglycosides during the first 6 h. For the highest clinically approved imipenem doses of 4 g per day, our Monte Carlo simulations predicted the unbound average steady-state concentrations to range from 7.61 to 22.6 mg/liter in adult critically ill patients (27).…”
Section: Methodsmentioning
confidence: 99%
“…A tobramycin concentration of 4 mg/liter and isepamicin concentrations of 8 to 16 mg/liter represent the average unbound plasma concentrations in humans over a 24-h dosing interval for tobramycin at 7 mg/kg of body weight and 15 or 25 mg/kg isepamicin given once daily (17,26). Additional experimental arms with 12 mg/ liter tobramycin and 64 mg/liter isepamicin represent the average free plasma concentration of aminoglycosides during the first 6 h. For the highest clinically approved imipenem doses of 4 g per day, our Monte Carlo simulations predicted the unbound average steady-state concentrations to range from 7.61 to 22.6 mg/liter in adult critically ill patients (27).…”
Section: Methodsmentioning
confidence: 99%
“…Concentrations of colistins A and B and their prodrugs, colistin methanesulfonate A and colistin methanesulfonate B, as well as tigecycline and imipenem, were measured using high-pressure liquid chromatography-tandem mass spectrometry (HPLC-MS/MS) (19)(20)(21). The maximum concentration of drug in serum (C max ), the area under the concentration-time curve from 0 h to 24 h (AUC 0 -24 ), the AUC 0 -ϱ for the free, unbound fraction of drug (fAUC 0 -24 ), the half-life (t 1/2 ), the cumulative percentage of a 24-h period that the drug concentration exceeds the MIC under steady-state pharmacokinetic conditions (%T MIC ), the AUC over 24 h in the steady state divided by the MIC for the free, unbound fraction of drug (fAUC/MIC), and the AUC/MIC value were obtained by a computer-assisted method (22).…”
Section: Methodsmentioning
confidence: 99%
“…A previous PD study in critically ill patients with VAP found that a 90% PTA achieving 40% T >MIC was observed at a MIC of 1-2 μg/mL when imipenem was administered by a 40 min infusion of 1 g q8h, whereas a continuous infusion of a daily dosage of 2 g of imipenem had a 90% PTA for achieving a target of 40% T >MIC at a MIC of 2-4 μg/ mL [8]. In the current study, the probability of a 4-h infusion regimen achieving a target of 40% fT >MIC were superior to a 1-h infusion regimen in an equivalent daily dosage of imipenem, therefore, a prolonged 4-h infusion regimen was a more effective strategy to achieve optimal PD exposure for pathogens with higher MIC than a 1-h infusion regimen.…”
Section: Pk Analysismentioning
confidence: 99%
“…It was found that a two-compartment model is adequate for describing distribution phase of imipenem [7,8], so it was employed in this study. Due to the high values of the rate constants in the differential equations, computation instabilities were expected, hence Taylor series expansion method [9] was used to solve the differential equations to avoid this problem by computing them until convergence of the final results was achieved.…”
Section: Pk Analysismentioning
confidence: 99%